2017
DOI: 10.1073/pnas.1700996114
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 potentiates the oncogenic effects of insulin by inhibiting the tumor suppressor DAB2IP

Abstract: Obesity and type 2 diabetes are significant risk factors for malignancies, being associated with chronic inflammation and hyperinsulinemia. In this context, insulin can synergize with inflammation to promote proliferation, survival, and dissemination of cancer cells. Point mutation of p53 is a frequent event and a significant factor in cancer development and progression. Mutant p53 protein(s) (mutp53) can acquire oncogenic properties that increase metastasis, proliferation, and cell survival. We report that br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
3
37
0
1
Order By: Relevance
“…Notably, mutant p53 can activate TNFα-induced NF-κB pathway through the transcriptional inhibition of the tumor suppressor DAB2IP, a cytoplasmic inhibitor of NF-κB and concomitantly hampering TNFα-induced activation of ASK1/JNK [162,163]. This dual effect orchestrated by mutant p53 increases the secretion of chemokines resulting in lymphocytes infiltration and severe inflammatory tumor microenvironment.…”
Section: Stimulation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Notably, mutant p53 can activate TNFα-induced NF-κB pathway through the transcriptional inhibition of the tumor suppressor DAB2IP, a cytoplasmic inhibitor of NF-κB and concomitantly hampering TNFα-induced activation of ASK1/JNK [162,163]. This dual effect orchestrated by mutant p53 increases the secretion of chemokines resulting in lymphocytes infiltration and severe inflammatory tumor microenvironment.…”
Section: Stimulation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Previous studies have demonstrated that the RAS-GTP enzyme-activated protein DAB2IP can combine with DAB2 to produce a specific protein complex, which can exert a negative regulatory effect on the ERK/MAPK signaling pathway (23)(24)(25). Research has been performed in recent years demonstrating that there is a low expression of DAB2IP in numerous malignant tumors, including prostate and breast cancer (26,27). Furthermore, additional studies have demonstrated that the downregulation of endogenous DAB2IP expression can enhance the proliferation of prostate and breast cancer (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not investigated this aspect, it is possible that DAB2IP inhibition is part of the mechanisms through which these miRNAs promote proliferation, survival, and motility of cancer cells. For instance, miR-96 and miR-92a were reported to activate PI3K/AKT/mTOR signaling [20,42], a phenotype potentially enhanced by DAB2IP loss [9].…”
Section: Discussionmentioning
confidence: 99%
“…Transwell migration and invasion assays were performed as described previously [8,9]. In experiments with conditioned medium, cells were pre-incubated with Ctrl or PC3conditioned medium for 24 h, and subsequently seeded in the presence of Ctrl or PC3-conditioned medium; the lower chamber of the transwell system was filled with high-serum medium.…”
Section: Cell Migration Invasion and Proliferation Assaysmentioning
confidence: 99%
See 1 more Smart Citation